Optimalisasi Pembenihan Ikan Nila Merah Nilasa Oreochromis sp. Di Ukbat Cangkringan, Yogyakarta - Andri Iskandar; Riza Septyanigar Islamay; Yudi Kasmono (Faculty of Science and Technology University Ibrahimy, 2021)
Abstract The aim of this study was to evaluate the optimization of Nilasa red tilapia fish Oreochromis niloticus breeding process at Work Unit Freshwater Aquaculture (WUFA) Cangkringan, Technology Development Center of Fisheries (TDCOF) Yogyakarta. Nilasa red tilapia fish is one of the commodity that has advantages, including respond to artificial feed, grow fast, can live with high density and resistance to disease. WUFA Cangkringan was one of the government fisheries center which develop nilasa red tilapia fish. The hatchery activities is including maintenance of the parentstock, spawning, larval rearing, harvesting and post harvest. Nilasa red tilapia fish was a test fish that used at the WUFA Cangkringan from red tilapia study and released under the name Nilasa in 2012, start from 1st generation (F-0) to the 5th generation (F-4) in the program selection. The survival rate resulting from the hatchery activities with seed 2-3 cm was 80% and the seed was sold at Rp50 fish-1. The profit obtained Rp150 699 688 year-1, R/C ratio 1,34 and payback period 9 month. Key word: nilasa red tilapia fish, breeding process, survival rate